Interpretation of Geothermal Magnetic Depths, Physicochemical Parameters and Heavy Metals Determination of Lamurde Hot-spring in the North-Eastern Benue Trough, Nigeria - Abdullahi, Mukaila; Valdon, Yunis B.; Andrew, Fartisincha P.; Abba, Adamu Usman; Maigari, Ibrahim (Earth and Planetary Science, 2023)
An integrated interpretation of the magnetic data and the analysis of physicochemical parameters and heavy metals from Lamurde hot spring has been done for the first time. The temperature of the hot spring was measured to be at 44 °C while the normal surface temperature is 25 °C. Three prominent magnetic anomalies were found at bottom depths of 11.379 ± 0.253 km, 13.015 ± 2.120 km and 9.161 ± 1.200 km suggesting that the Lamurde hot-spring is heated at deep mantle (13.015 ± 2.120 km) and issued to the surface through either local or regional fault system or both. The physicochemical analysis gave pH (7.93 ± 0.06), total chlorine (125.0 ± 2.89 µg/L), total dissolved solids TDS (202.0 ± 2 ppm), hardness (64 ± 1.73 µg/L), alkalinity (210 ± 4 µg/L) and nitrate (1.3 ± 0.3 µg/L). In comparison with that of WHO standards, the results indicated that all the physicochemical parameters studied except for alkalinity fall within the permissible limits. Heavy metals were identified and analyzed in the sampled water: lead (0.1501 ± 0.0007 mg/L), chromium (0.0729 ± 0.0007 mg/L), nickel (0.1987 ± 0.1476 mg/L), cadmium (0.0115 ± 0.0003 mg/L), copper (0.0442 ± 0.0008 mg/L), arsenic (0.0456 ± 0.0003 mg/L), iron (0.8016 ± 0.0005 mg/L), cobalt (0.0274 ± 0.0004 mg/L), selenium (undetectable), manganese (5.31 ± 0.0361 mg/L) and zinc (0.1629 ± 0.0004 mg/L). The concentrations of heavy metals observed in the area with the exception of Zn, Cu and Se are all above the standards for drinking water. Their concentrations are in the order of Mn > Fe > Ni > Zn > Pb > Cr > As > Cu > Co > Cd > Se. These results suggest that the Lamurde hot spring is a potential zone for Mn, Fe, Ni, Zn and Pb deposit. ER